TINJAUAN HUKUM PERLINDUNGAN KONSUMEN DAN PERSAINGAN USAHA DALAM PEMANFAATAN BIG DATA MARKETPLACE DI INDONESIA - Widadatul Ulya (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2022)
The digital era has an impact on the rapid growth of the marketplace. Through the marketplace, traders can target international markets only by marketing their products digitally. The growth of the marketplace cannot be separated from the value of consumer satisfaction in increasing purchasing power, because consumer satisfaction is the key to public trust. To provide satisfaction to consumers, business actors utilize big data technology. The use of consumer big data ultimately brings positive and negative impacts for consumers themselves and also business actors. This normative juridical research with the type of library research is carried out to see a review of business law on the use of consumer marketplace big data. This research is important because digital business is growing and developing rapidly in various sectors, one of which is the trade sector through a marketplace platform that utilizes big data. As a result, the preventive efforts that have been carried out so far through the implementation of laws and regulations have not been effective in protecting the interests of consumers, so the role of the Legal Aid Institute and the Consumer Dispute Settlement Agency is needed to support consumer protection. The healthy business competition climate also still needs to be improved, of course with the role of the Business Competition Supervisory Commission, given the limitations of the Business Competition Law which does not yet apply the principle of extraterritoriality